Characterization of the complete mitochondrial genome of Amblyomma ovale, comparative analyses and phylogenetic considerations - Uribe, Juan E. (2020)
In this study, we sequenced two complete mitochondrial genomes of Amblyomma ovale, a tick of public health importance. Sequencing two distinct individuals, the resulting mitochondrial genomes were 14,756 and 14,760 bp in length and maintained the same gene order previously reported in Amblyomma. These were combined with RNA-seq derived mitochondrial sequences from three additional species, Amblyomma aureolatum, Amblyomma maculatum, and Amblyomma moreliae, to carry out mitogenome comparative and evolutionary analyses against all previously published tick mitochondrial genomes. We described a derivative genome rearrangement that isolates Ixodes from the remaining Ixodidae and consists of both a reverse translocation as well as an event of Tandem Duplication Random Loss. Genetic distance analyses indicated that cox2, nd1, nd5, and 16S are good candidates for future population studies in A. ovale. The phylogenetic analyses corroborated the utility of complete mitochondrial genomes as phylogenetic markers within the group. This study further supplements the genome information available for Amblyomma and facilitates future evolutionary and population genetic studies within the genus.